Land of Dreams : Greek and Latin Studies in Honour of A.H.M. Kessels - Poel, van der; Hunink, Vincent; Lardinois, André (Brill Book Archive Part 1, ISBN: 9789004472495., 2006)
This collection of essays by twenty-eight Dutch scholars is intended as a tribute to prof. dr. A.H.M. Kessels on the occasion of his retirement as professor of Greek Language and Literature at the Radboud University Nijmegen (Netherlands). It reflects his broad interests in the entire field of classical scholarship, ranging from early Greek poetry to later Latin literature and the reception of classics in modern literature. At the same time, the volume singles out some areas for special interest, notably dreams in classical literature (6 essays), classical drama (7 essays), the reception of Homer (4 essays), Greek literature (5 essays) and Latin literature (6 essays). The collection as a whole may be considered a sampler attesting the breadth and depth of present-day classical scholarship in the Netherlands. With contributions by G.J.M. Bartelink; A.A.R.Bastiaensen; L.J. ter Beek; L. de Blois; J. den Boeft; B.M.C. Breij; J.M. Bremer; J.N. Bremmer; J.H. Brouwers; A.M. van Erp Taalman Kip; A. Harder; A.J.L. van Hooff; P. v.d. Horst; V.J.Chr. Hunink; I.F.J. de Jong; A.P.M.H. Lardinois; E.M. Moormann; A.P. Orbán; M.G.M. van der Poel; R.P. Salomons; D.M. Schenkeveld; W.L.G.M. Slenders; H. van Tress; G.C. Wakker; H.T. Wallinga; J.H. Waszink; M.J.H. van der Weiden.